Perencanaan dan Pemasangan Sistem Instalasi Penerangan di Kawasan Wisata Sunset Pantai Paradiso Kelurahan Oesapa Barat, Kecamatan Kelapa Lima, Kota Kupang - Sulaiman A Sulaiman A; David Suban Koten; Maria D. Badjowawo; Muchamad Ali; Fransiskus Seda; Yudi A.H. Berry; Daniel Umbu Ndina (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
The Paradiso Beach tourist attraction is a gathering place for several MSMEs in the Oesapa area, located on Jalan Timor Raya, West Oesapa, Kupang City. Several MSMEs at this tourist attraction utilize the land surrounding the Paradiso Beach sunset attraction to sell their processed products. The location can accommodate MSMEs from the West Oesapa Village and its surroundings. It can accommodate approximately 100 MSMEs, with six currently operating there. Vendors at the Paradiso Beach tourist attraction provide processed agricultural staples such as fried and boiled corn, green beans, cassava, bananas, vegetables, and various culinary snacks such as cassava chips, banana chips, fried corn, cakes, and drinks. To survive and thrive, MSMEs must have a distinctive identity, both in terms of taste, product packaging, logo, and packaging color, so that when marketed, these products have a unique appeal to buyers. Currently, MSMEs located in the coastal tourist attraction are not yet well-known in the city of Kupang, because the traders themselves still market traditionally, there is no promotional media, product packaging still uses thin plastic, existing culinary foods have not been packaged so that food becomes more durable and food hygiene is not guaranteed. On the other hand, the sales place is still very simple, where the local community builds their own sales stalls with makeshift lighting systems, so that at night sales activities are not optimal, thus this can also be one of the factors causing slow culinary sales by the local community Starting from these problems, we from the D4 Electrical Installation Study Program, Department of Electrical Engineering, Kupang State Polytechnic have provided solutions to the problems experienced by the MSME community around the Paradiso Beach sunset tourist area by carrying out Planning and Installation of Lighting Systems to Support Culinary Businesses in the Paradiso Beach Eco-Tourism Area, West Oesapa Village, Kelapa Lima District, Kupang City.